A New Removable Uterine Compression by a Brace Suture in the Management of Severe Postpartum Hemorrhage - Aboulfalah, Abderrahim; Fakhir, Bouchra; Ait Ben Kaddour, Yassir; Asmouki, Hamid; Soummani, Abderraouf (Frontiers in Surgery, 2014)
Post-partum hemorrhage (PPH) is a life threatening complication of delivery. It is the first cause of maternal mortality. During those last 15 years, several total uterine compressive sutures were described in literature. They have proven their effectiveness and safety in management of severe PPH as an alternative to hysterectomy. We present with this paper a new technique of uterine compressive sutures based on removable uterine brace compressive sutures with compression of the uterus against the pubis. This technique may be more effective by using tow mechanisms of uterine bleeding control and also may prevent uterine synechia by respecting uterine cavity and the removal of the suture one or two days later. We present also results of 15 patient’s series experiencing this new sutures.